Nitrogen fixation among boreal feather mosses along a clear-cut chronosequence - Wik Persson, Lisa (SLU/Dept. of Forest Ecology and Management, 2013)

(untitled)
The Swedish boreal forests are limited by nitrogen (N) availability. While biological N2 fixation by cyanobacteria hosted by pleurocarpous feather mosses are important sources of N input to natural boreal forest ecosystems, little is known about the patterns of N2 fixation in silvicultural systems. This study investigates the biological N2 fixation rates of two boreal feather moss species (Pleurozium schreberi and Hylocomium splendens) along a chronosequence from clear-cut to mature forest, as well as the vegetation characteristics along the chronosequence. Measurements and samples were collected from 32 forest sites that were classified into four age classes (clear-cut, pre-commercially thinned, thinned and mature forest). The sites were located near the city of Arvidsjaur in northern Sweden. Moss, dwarf shrub and grass biomass were determined at each forest site and gametophytes of P. schreberi and H. splendens were collected for acetylene reduction analysis. The results showed that the biomass of P. schreberi was significantly higher in pre-commercially thinned and thinned stands than in clear-cuts while H. splendens had a much lower biomass that did not change over time. The total N2 fixation rate varied between 0.1-1.4 kg N2 ha-1 yr-1 and was highest in pre-commercially thinned and thinned stands. The results from this study shows that naturally occurring biological N2 fixation vary manifold across managed forest stands. It also suggests that forest management can be used as a tool to modify biological N2 input to N limited silvicultural systems, although further studies will be needed to determine its impact on soil fertility and effectiveness in supporting tree growth.